Highly Stable, Cold-Active Aldehyde Dehydrogenase from the Marine Antarctic Flavobacterium sp. PL002 - Georgiana Necula-Petrareanu; Paris Lavin; Victoria Ioana Paun; Giulia Roxana Gheorghita; Alina Vasilescu; Cristina Purcarea (Fermentation, 2021)
Stable aldehyde dehydrogenases (ALDH) from extremophilic microorganisms constitute efficient catalysts in biotechnologies. In search of active ALDHs at low temperatures and of these enzymes from cold-adapted microorganisms, we cloned and characterized a novel recombinant ALDH from the psychrotrophic Flavobacterium PL002 isolated from Antarctic seawater. The recombinant enzyme (F-ALDH) from this cold-adapted strain was obtained by cloning and expressing of the PL002 aldH gene (1506 bp) in Escherichia coli BL21(DE3). Phylogeny and structural analyses showed a high amino acid sequence identity (89%) with Flavobacterium frigidimaris ALDH and conservation of all active site residues. The purified F-ALDH by affinity chromatography was homotetrameric, preserving 80% activity at 4 °C for 18 days. F-ALDH used both NAD+ and NADP+ and a broad range of aliphatic and aromatic substrates, showing cofactor-dependent compensatory KM and kcat values and the highest catalytic efficiency (0.50 µM−1 s−1) for isovaleraldehyde. The enzyme was active in the 4–60 °C-temperature interval, with an optimal pH of 9.5, and a preference for NAD+-dependent reactions. Arrhenius plots of both NAD(P)+-dependent reactions indicated conformational changes occurring at 30 °C, with four(five)-fold lower activation energy at high temperatures. The high thermal stability and substrate-specific catalytic efficiency of this novel cold-active ALDH favoring aliphatic catalysis provided a promising catalyst for biotechnological and biosensing applications.